2013
DOI: 10.4028/www.scientific.net/amr.668.584
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interior Ballistic Prediction of Gun Propellants Based on Experimental Pressure-Apparent Burning Rate Model in Closed Vessel

Abstract: A new experimental pressure-apparent burning rate model was established based on the recorded pressure-time data in the closed vessel to study the actual burning gas generate rate of a propellant whose form function is not available. The new burning model can replace the Vieille’s law and form function of propellants in the interior ballistic equations to predict the interior ballistic performance of gun. As distinct from the traditional geometric form function based burning rate model, the new model introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Each sleeve was cleaned by ethanol and acetone repeatedly, then dried at 110 8C for 30 min. The closed bomb burning tests of modified propellants were performed using a 100 cm 3 vessel, which is similar to a previously reported device [14]. To determine the force constant of propellant, each sample was tested for three times with the loading density of 0.12 g/cm 3 and 0.2 g/cm 3 , respectively.…”
Section: Propellant Erosion Testing and Closed Vessel Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each sleeve was cleaned by ethanol and acetone repeatedly, then dried at 110 8C for 30 min. The closed bomb burning tests of modified propellants were performed using a 100 cm 3 vessel, which is similar to a previously reported device [14]. To determine the force constant of propellant, each sample was tested for three times with the loading density of 0.12 g/cm 3 and 0.2 g/cm 3 , respectively.…”
Section: Propellant Erosion Testing and Closed Vessel Experimentsmentioning
confidence: 99%
“…, it can be found that abundant asperities are arranged on the microsphere surface. According to our previous study [14], they are nanoparticles deriving from the recipe. Figure 2(c) illustrates that the particle size distribution of the nanocomposites is in the range of 4-40 mm with an average value of 11.9 mm, which is well-indexed to the SEM results.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the overall fraction of a propellant burnt(∅) the web fraction is utilized as well as a shape function( ) which takes into account the complex geometries of various grains. Recently a novel approach was developed to predict burn rates in gun propellants without the use of shape functions (Xiao et al, 2015) but the traditional calculation outlined in Equation (1) is still utilized in the majority of internal ballistic calculations (Kulkarni and Maik, 2000):…”
Section: Introductionmentioning
confidence: 99%